Working and nursing: navigating job and breastfeeding demands at work. Issue 4 (8th August 2017) - Johnson, Katherine M.; Salpini, Colleen
ABSTRACT: Breastfeeding is a sex-specific, work–family issue for women. Yet, there is relatively little sociological research on the breastfeeding-work interface. What challenges do breastfeeding women face during the workday? (How) Are some more successful than others at merging breastfeeding and work? We conducted interviews with 22 US women as part of a case study of workplace breastfeeding support. The Patient Protection and Affordable Care Act [PPACA] (2010) includes breastfeeding provisions, but primarily address hourly workers. Most women in our study were not covered by the PPACA but had access to a workplace Breastfeeding Support Initiative. Despite this, women faced several challenges: different degrees of schedule control, unequal access to space, and unexpected breastfeeding demands. Women also had differential access to workplace resources to cope with demands. Control over both time and space was a cross-cutting theme. Research needs to better address work conditions that are conducive to breastfeeding rather than simply asking if work and breastfeeding are incompatible. Furthermore, workplace support initiatives will succeed only to the extent that they can directly address work conditions, even if on a temporary basis.